2014
DOI: 10.3402/ijch.v73.22691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pneumococcal vaccines use on invasive pneumococcal disease in Nunavik (Quebec) from 1997 to 2010

Abstract: BackgroundIn 2000, an outbreak of severe pneumonia caused by a virulent clone of serotype 1 Streptococcus pneumoniae was detected in the Nunavik region of Quebec. A mass immunization campaign was implemented in the spring of 2002, targeting persons ≥5 years of age and using the 23-valent pneumococcal polysaccharide vaccine (PPSV23). At the same time, the 7-valent pneumococcal conjugate vaccine (PCV7) was introduced into the routine immunization programme of infants, with catch-up for children up to 4 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…(6) Although invasive pneumococcal disease may occur with all serotypes, almost 60% of cases are caused by the same 23 serotypes. (7, 8) Furthermore, certain serotypes seem to be more commonly isolated from specific organ systems. For instance, serotype 1 and 3 are more frequently isolated in pneumonia and serotypes 6, 10 and 23 are regularly isolated in meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Although invasive pneumococcal disease may occur with all serotypes, almost 60% of cases are caused by the same 23 serotypes. (7, 8) Furthermore, certain serotypes seem to be more commonly isolated from specific organ systems. For instance, serotype 1 and 3 are more frequently isolated in pneumonia and serotypes 6, 10 and 23 are regularly isolated in meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the introduction of a 7-valent pneumococcal conjugate vaccine (PCV7) in 2002 and the 13-valent vaccine (PCV13) in 2010 in Northern Canada, pneumococcal pneumonia remains a major issue ( 5 ). Studies examining the effect of PCV7 in Northern communities have found that while there has been a decrease in invasive pneumococcal disease caused by serotypes included in the vaccine, there was an increase in disease caused by serotypes not included in PCV7 ( 6 , 7 ). A number of risk factors have been associated with respiratory disease prevalence and/or severity in Inuit children, including household overcrowding, passive and in utero smoke exposure, lack of breastfeeding and reduced ventilation in the house ( 8 , 9 ).…”
mentioning
confidence: 99%
“…To date, 98 different serotypes of S. pneumoniae were identified, with 23 of them being the major cause of invasive pneumococcal diseases [ 20 , 21 ]. The most common isolate is serotype 14, followed by 1, 5, 6A, 6B, 19F, 23F serotypes, which can be found in more than 50% of patients [ 22 ].…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%